Non-genetic factors in reproductive and growth indicators of buffalo cows Bubalus bubalis in the Granma province, Cuba - M?ndez, Mildred; Fraga, Luis Mateo (Cuban Journal of Agricultural Science, 2010)
Observations (255 to 368) of four herds located in two municipalities of the Granma province, Cuba, were used to determine non-genetic factors affecting the productivity in river buffaloes. The data were processed by GLM (General Linear Model) of SAS through four linear models of fixed effects, including: four herds, nine calving years, two calving seasons (in season July-October and out of season November- June), sex of the calf, and age at first calving (linear, quadratic, and cubic) as concomitant variable. The traits were: weight of calves at birth (kg) and at weaning (kg), service period (d), and interval between calvings (d). General means of 36.4 ? 0.1 kg, 121 ? 0.3 kg, 70 ? 0.5 d, and 392 ? 0.5 d, respectively, were obtained. The model with highest coefficient of determination considered the effects: herd, calving year, previous calving season, calf sex, and adjustment by regression (linear, quadratic, and cubic) in the age at first calving. The general indicators obtained in the Granma province were within the range reported for the country by the Ministry of Agriculture. When analyzing the coefficients of partial determination, the greatest contributions to the total variance were determined by the effect of the year (58.82 %), followed by the effect of the herd (18.38 %). The rest was between 7.72 and 1.84 %. The application of corrections are recommended for the general management of the productive units (mainly feeding) allowing the increment in the indicators. Key words: buffalo, environmental factors, birth weight, reproductive.